IFRS ADOPTION AND EARNINGS MANAGEMENT PRACTICE: EVIDENCE FROM INDONESIA COMPANIES - Vina Kholisa Dinuka (JURNAL AKUNTANSI, EKONOMI dan MANAJEMEN BISNIS, 2019)
The purpose of this study is to verify IFRS contribution by examining the presence of Accrual Earnings Management (AEM) and Real Earnings Management (REM) in the period pre- and post- IFRS implementation in manufacturing companies in Indonesia. AEM is measured by absolute value of discretionary accrual, while REM is proxied by three measurements of REM, they are abnormal cash flow operation, abnormal production and abnormal discretionary expenses. The sample is taken from Indonesia stock exchange in 2009-2011 and 2013-2015. 2012 is Indonesia adoption period and it is excluded from the sample, because it is considerated as transitory year. This study uses regression analysis and Paired t-test to compare the presence of AEM and REM preceding and following IFRS implementation. The findings reveal that IFRS adoption has significantly negative effect towards AEM and REM. It indicates that the following IFRS implementation, AEM and REM are decrease. Therefore, IFRS is able to reduce earnings management practices in manufacturing companies in Indonesia both for AEM and REM.